A new species of Formicivora antwren from the Chapada Diamantina, eastern Brazil (Aves: Passeriformes: Thamnophilidae) - Gonzaga, Luiz Pedreira; Carvalhaes, André M.p.; Buzzetti, Dante R.c. (Zootaxa, 2007)
Formicivora grantsaui sp. nov. (Sincorá Antwren) is described from a series of specimens from the valley of the Rio Cumbuca (12 o 58’29”S, 41 o 21’29”W, elevation 860 m), 3.5 km northeast of Mucugê, Bahia, Brazil, and adjacent areas. It is more closely related to F. acutirostris, F. grisea, and F. rufa than to other species of the genus, differing from them by a combination of plumage and vocal characters. The new species is known only from the campo rupestre vegetation of the Serra do Sincorá between 850 m and 1100 m in the Chapada Diamantina, which is part of the Espinhaço Range, a distinctive area of endemism for birds and other groups of organisms in South America. In places it occurs sympatrically with F. rufa, but the two occupy different habitats.